2017
DOI: 10.7589/2016-05-103
|View full text |Cite
|
Sign up to set email alerts
|

Sheep-Associated Malignant Catarrhal Fever–Like Skin Disease in a Free-Ranging Bighorn Sheep (Ovis canadensis), Alberta, Canada

Abstract: Malignant catarrhal fever-like clinical disease was diagnosed in a free-ranging bighorn sheep ( Ovis canadensis ) from Alberta, Canada, in June 2015. Antemortem and gross pathology findings included muscle atrophy, marked weight loss, and bilaterally symmetric alopecia with hyperpigmentation and crusting over the face, medial surfaces of the pinnae, dorsal trunk, distal limbs, perineal area, and tail. Histologically, the skin lesions were characterized by granulomatous mural folliculitis with numerous multinuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…22,30 The cutaneous lesions observed in this case series had similar macroscopic characteristics between all 16 goats, and were consistent with previous reports of caprine GMF, 10,45 and GMF in other ruminant animal species. 4,11,24,28,44 Although reports of GMF in MCF-infected cattle are rare, other cutaneous lesions are relatively common as a part of the systemic disease process in classic vasculocentric MCF, and are increasingly prominent with greater chronicity. 4,24 Cutaneous lesions seen with typical chronic MCF in cattle feature many of the same gross characteristics described in this caprine GMF case series, such as crusting, alopecia, and erosion.…”
Section: Discussionmentioning
confidence: 99%
“…22,30 The cutaneous lesions observed in this case series had similar macroscopic characteristics between all 16 goats, and were consistent with previous reports of caprine GMF, 10,45 and GMF in other ruminant animal species. 4,11,24,28,44 Although reports of GMF in MCF-infected cattle are rare, other cutaneous lesions are relatively common as a part of the systemic disease process in classic vasculocentric MCF, and are increasingly prominent with greater chronicity. 4,24 Cutaneous lesions seen with typical chronic MCF in cattle feature many of the same gross characteristics described in this caprine GMF case series, such as crusting, alopecia, and erosion.…”
Section: Discussionmentioning
confidence: 99%
“…The disease forms range from acute severe inflammatory disease with a short clinical course to a more chronic syndrome occasionally with skin form (13). The summarized symptoms of MCF in cattle are marked with high fever, depression, anorexia, conjunctivitis, corneal opacity, lymphadenopathy, ulceration and erosions of the upper digestive and respiratory systems, and neurological disorders, in chronic cases weight loss, muscle atrophy and bilaterally symmetric alopecia (13,14).…”
mentioning
confidence: 99%
“…7 Although there is a long-held belief that OvHV-2 does not cause disease in sheep, histologic lesions consistent with MCF have been observed occasionally in both domestic and wild sheep. 5,15 The fact that MCF-like disease can be induced in sheep by experimental inoculation of OvHV-2 suggests that MCF can also occur in sheep following natural infection. 9 Because almost all sheep have life-long infection with OvHV-2, detection of antibodies to OvHV-2 or viral DNA in a clinically affected sheep has little value to confirm the diagnosis of MCF.…”
mentioning
confidence: 99%
“…A 2017 published report of a MCF-like skin disease in a free-ranging bighorn sheep, another natural OvHV-2 reservoir host, identified higher levels of OvHV-2 DNA in affected skin relative to unaffected skin. 15 In addition, studies in bison and rabbits with experimentally induced SA-MCF revealed that OvHV-2 DNA levels are positively correlated with lesion severity scores. 3,4 In order to determine if there was a similar association in the clinically affected lamb described in our study, tissue lesions were scored using a score criterion previously developed for bison with MCF.…”
mentioning
confidence: 99%
See 1 more Smart Citation